Personalized Photo Enhancement Using Artificial Neural Network - Dela Cruz, Jennifer C.; Garcia, Ramon G.; Magwili, Glenn V.; Cordon, Jerico C.; Suplico, Jesser Paul P; Sauli, Zaliman (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Artificial Neural Network (ANN) is applied to create a photo enhancement program that automatically adjusts image parameters on the face based on the preference of its own user. Viola Jones algorithm was used for face detection, and a Graphical User Interface (GUI) is created to enable users to edit the photos easily. Input data sets are essential in the learning progress of ANN. Variety of users inputted their respective image data into the program for training the neural network. Regression plot developed will be used to determine the performance of the system. The authors would relate the consistency of the users in editing their photos to the produced regression plot. On the other hand, actual tests were conducted to determine the time spent editing the photos manually and the amount of time the system automatically adjusted the photo. There is a difference in editing time between average manual adjustment and automatic adjustment by the ANN.